Peran Arus Kas Aktivitas Operasi dalam Memperkuat Hubungan ESG dan Kinerja Perusahaan - Pertiwi, Meilani Intan; Ardhana Reswari Hasna Pratista; Irnin Miladdyan Airyq; Kholidil Amin (P3M Politeknik Negeri Bengkalis, 2025)
This study delves into the role of environmental, social, and government (ESG) in company performance. In addition, this study also examines the role of operational cash flow in strengthening the relationship between ESG and company performance. Based on the results of previous research, operational cash flow is strong capital for companies before making long-term investments in ESG. This research model was tested using multiple regression analysis with qualitative data. The sample of this study was companies from all sectors in Indonesia in the 2020-2024 period, using the purposive sampling method. The number of samples obtained in this study was 263 observations. The results of this study are that social responsibility and governance practices affect company performance. Operational cash flow strengthens the relationship between environmental impact and company performance. This finding indicates that environmental impact in Indonesia does not affect company performance because it does not have strict regulatory pressure. However, environmental impact will significantly affect company performance if the company's operational cash flow is substantial.